The addition of Bi2WO6 nanoparticles to polyvinyl alcohol film: Improvements in optical, mechanical, and electrical properties - Beyazay, Emre; Sahin, Nazlican; Karabul, Yasar; Kilic, Mehmet; Ozdemir, Zeynep Given (ELSEVIER, 2025)
This study deals with the influence of adding Bi2WO6 (BWO) nanoparticles on the optical, structural, dielectric, and mechanical properties of polyvinyl alcohol (PVA). BWO nanoparticles synthesized by solvothermal method were characterized by X-Ray diffraction (XRD) and scanning electron microscope (SEM-EDS). The thick film nanocomposites were analyzed by Fourier Transformed Infrared (FTIR) spectrometer, XRD device, SEM, atomic force microscope (AFM), ultraviolet visible (UV-Vis) spectrophotometer, impedance analyzer, and tensile test machine. While FTIR analyses confirmed the formation of composite structure and the presence of BWO in the composites, AFM views indicated the reduced roughness for composites. Additionally, the UV-Vis light absorption spectra revealed a narrowed band gap in the composites. Moreover, with increasing BWO contribution, gradual increases were recorded in Young's modulus, toughness and % breaking strain parameters. The frequency dependent dielectric properties was also shown that the energy storage ability of the PVA matrix enhances 25 % and 50 % due to 2 % and 3 % BWO additives, respectively. However, the composite with higher epsilon ' and lower epsilon '' values than the pure PVA in the entire frequency range was the 2 % BWO-doped nanocomposite. Based on the serious and simultaneously improvements in electrical, optical and mechanical properties, it can be suggested that 2 % BWO additive provides the opportunity to expand the application area of PVA synergistically.
Keywords: Polyvinyl alcohol; Bi2WO6; Band gap; Energy storage; Mechanical durability; POLY(VINYL ALCOHOL); DIELECTRIC-PROPERTIES; HIGH-PERFORMANCE; FACILE SYNTHESIS; NANOCOMPOSITES; CRYSTALLINITY; CONDUCTIVITY; Physics